2009
DOI: 10.1111/j.1475-4932.2009.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Education Prejudiced by Country‐Risk?

Abstract: We consider country-risk as a determinant of education growth in a panel of countries. Applying cross-country dynamic panel data estimations, we show that among the different levels of education, the secondary is the most affected, followed by the tertiary. When different single measures of risk are considered one by one, the tertiary education is affected by more types of risk than any other level of education. This contributes to the literature on the educational production function, as it adds a robust dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Hanushek and Woessmann (2011) concluded that there is very little evidence in support of the influence of inputs in cross-country differences in schooling achievements while recognizing the essential effects of family and social background and of some countryspecific school-related institutions. For example, Sequeira and Ferraz (2009) and Sequeira (2009) highlight the significant effect that country-risk has in education measures, and Galor and Klemp (2014) analyse the biocultural origins of human capital formation, using an extensive genealogical record for nearly half a million individuals in Quebec from the 16 th to the 18 th century, highlighting the importance of the choice toward child quality in the process of evolution of human capital through history.…”
Section: Introductionmentioning
confidence: 99%
“…Hanushek and Woessmann (2011) concluded that there is very little evidence in support of the influence of inputs in cross-country differences in schooling achievements while recognizing the essential effects of family and social background and of some countryspecific school-related institutions. For example, Sequeira and Ferraz (2009) and Sequeira (2009) highlight the significant effect that country-risk has in education measures, and Galor and Klemp (2014) analyse the biocultural origins of human capital formation, using an extensive genealogical record for nearly half a million individuals in Quebec from the 16 th to the 18 th century, highlighting the importance of the choice toward child quality in the process of evolution of human capital through history.…”
Section: Introductionmentioning
confidence: 99%